Tinjauan Yuridis terhadap Perbuatan Melawan Hukum yang Dilakukan oleh Notaris dan Kreditur dalam Pembuatan Akta Autentik: Studi Putusan Nomor :1048/PK/PDT/2022 - Eklesia Novita Alverin Siagian; Hasim Purba; Sutiarnoto (Jurnal Hukum Lex Generalis, 2025)
A notary is a Public Official who is authorized to make Authentic Deeds. Notary in carrying out his/her position as a public official, when making a deed may include data or information originating from a fake letter/document into the deed. This incident can have legal consequences for both the deed made and the Notary who made the deed. The problem in this study is the unlawful act committed by the notary and the creditor in making an authentic deed. The Notary's liability for the authentic deed is in accordance with the decision. The research method used in this study is the type of Normative Juridical research. Normative Legal Research is a process of determining legal rules, legal principles, and legal doctrines to answer the legal problems faced. The Notary's liability in the event of an Perbuatan Melawan Hukum (PMH) on a deed depends on the problem at hand. If the Notary is proven to have committed an Unlawful Act together with one of the Applicants, then the Notary and the Applicant will bear all losses incurred on the deed, then the liability for the unlawful act is not only limited to liability for losses but also criminal liability.